Simulasi transfer panas pada dinding dengan software Therm 7.7 (ARTEKS : Jurnal Teknik Arsitektur, 2019)
Heat transfer simulation on the wall with Thermal 7.7 software Counting the heat transfer in building is not something complicated. There are quite a lot of computer simulation software offering precision and variants which meet the needs of the users. Software Therm offers one advantage, which is user-friendly, and can be used for a real plane in building   design and can even be used to count the heat transfer in a building map. The difficulty in using this application is the limitation in building material library which is suitable for daily building materials in Indonesia. However, this software allows the users to add building material library by filling in with building material value in connection with simple therm. This research is based on the internal research funded by Soegijapranata Catholic University, the aim of which is to analyze the field of wall materials by utilizing Software Therm with real heat transfer simulation and accurate calculation by mapping plane wall cutting. This research is based on the internal research funded by Soegijapranata Catholic University, the aim of which is to analyze the field of wall materials by utilizing Software Therm with real heat transfer simulation and accurate calculation by mapping plane wall cutting. Descriptive research design is applied to describe the heat transfer through walls by using software Therm and the effects of the heat transfer toward the inside room so that it can provide positive response to anticipate thermal effects entering the building. The finding of this research is expected to be able to become the basis for building design which must give special attention to the direction of building orientation so that the heat transfer of the effects of sunlight toward the wall can be found and be wisely anticipated.© 2019 Leonardus Murialdo Fransiskus Purwanto
Keywords: Building facade; Heat transfer; Therm software